The effectiveness of constructive learning strategy in achieving art education for sixth-grade primary students (Journal of the College of Basic Education, 2022)
The aim of the research is to find out the effectiveness of the constructivist learning strategy in achieving the subject of artistic education for sixth graders. The researcher used the experimental design with two independent and equal groups. The research sample was randomly chosen from the sixth grade primary students and the researcher chose Division (A) to represent the experimental group that is taught according to structural learning, and Division B represented the control group that is taught in the traditional way. Students (40) male and female students, with (20) male and female students in each division. The researcher prepared the research tool (the skill test), validation was verified and the tool was stable and used the T-test to statistically process the data. The results showed the superiority of the students of the experimental group that studied The content of Technical Rbia using Strategy on learning constructivist according to the content prepared in instructional plans (artistic expression) according to the skill of the post test on pupils control group peers.